Penilaian Kinerja sebagai Alat Pengembangan SDM - Mareta Nafizatul Lailil; Chelsea Patrecia; Virnala Gizka Ameliya; Maya Eka Pradita; Maulana Wahyu Firmansyah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Performance appraisal is one of the important elements in human resource management (HR) which aims to measure the contribution and effectiveness of employees in achieving organizational goals. In addition to its function as an evaluation tool, performance evaluation also has a strategic role as a means of human resource development. With a structured and data-driven approach, performance appraisals help identify employee strengths and weaknesses, provide constructive feedback, and design appropriate training and development programs. This article describes the basic concepts, methods and benefits of performance appraisal to support individual and organizational development. The focus is on the importance of creating a fair, transparent and sustainable evaluation system to create a productive work environment that focuses on development. Therefore, performance appraisal is not just a measuring tool, but also a driver of change to realize the maximum potential of HR functions.